A Biostable l‐DNA Hydrogel with Improved Stability for Biomedical Applications. Issue 30 (10th June 2022) - Yang, Bo; Zhou, Bini; Li, Cuifeng; Li, Xiaowei; Shi, Ziwei; Li, Yuxin; Zhu, Chenyou; Li, Xin; Hua, Yi; Pan, Yufan; He, Jian; Cao, Tianyang; et al.
Abstract: DNA hydrogels have attracted increasing attention owing to their excellent permeability and high mechanical strength, together with thixotropy, versatile programmability and good biocompatibility. However, the moderate biostability and immune stimulation of DNA have arisen as big concerns for future potential clinical applications. Herein, we report the self‐assembly of a novel l ‐DNA hydrogel, which inherited the extraordinary physical properties of a d ‐DNA hydrogel. With the mirror‐isomer deoxyribose, this hydrogel exhibited improved biostability, withstanding fetal bovine serum (FBS) for at least 1 month without evident decay of its mechanical properties. The low inflammatory response of the l ‐DNA hydrogel has been verified both in vitro and in vivo. Hence, this l ‐DNA hydrogel with outstanding biostability and biocompatibility can be anticipated to serve as an ideal 3D cell‐culture matrix and implanted bio‐scaffold for long‐term biomedical applications. Abstract : An l ‐DNA hydrogel is reported with the outstanding shear‐thinning, self‐healing and thermal‐responsiveness properties of d ‐DNA hydrogels based on the same network topology and supramolecular interactions. Additionally, with the mirror‐isomer deoxyribose, this hydrogel exhibited excellent biostability and stimulated low inflammation. These advances will greatly promote the feasibility of real‐world applications.